Flexible ERP for Construction Company with Petri Net Model - Masca Indra Triana; Berlian Al Kindhi (Unusa Press, 2020)
Prospectively, the existence of the construction service industry, both small and large scale, has strategic value for Indonesia, considering that the proportion of its role is quite large and involves the large number of workers involved in the implementation of a construction project. From the above statement, it can be concluded that construction service companies have a positive impact on economic development. But in reality, the implementation of a construction service business has several obstacles and problems. According to the Report on Construction Development